Microsomal triglyceride transfer protein -164 T > C gene polymorphism and risk of cardiovascular disease: results from the EPIC-Potsdam case-cohort study - di Giuseppe Romina; Pechlivanis Sonali; Fisher Eva; Arregui Maria; Weikert Beate; Knüppel Sven; Buijsse Brian; Fritsche Andreas; Willich Stefan N; Joost Hans-Georg; Boeing Heiner; Moebus Susanne; et al. (BMC, 2013)
Abstract Background The microsomal triglyceride transfer protein (MTTP) is encoded by the MTTP gene that is regulated by cholesterol in humans. Previous studies investigating the effect of MTTP on ischemic heart disease have produced inconsistent results. Therefore, we have tested the hypothesis that the rare allele of the -164T > C polymorphism in MTTP alters the risk of cardiovascular disease (CVD), depending on the cholesterol levels. Methods The -164T > C polymorphism was genotyped in a case-cohort study (193 incident myocardial infarction (MI) and 131 incident ischemic stroke (IS) cases and 1 978 non-cases) nested within the European Prospective Investigation into Cancer and Nutrition (EPIC)-Potsdam study, comprising 27 548 middle-aged subjects. The Heinz Nixdorf Recall study (30 CVD cases and 1 188 controls) was used to replicate our findings. Results Genotype frequencies were not different between CVD and CVD free subjects (P = 0.79). We observed an interaction between the -164T > C polymorphism and total cholesterol levels in relation to future CVD. Corresponding stratified analyses showed a significant increased risk of CVD (HRadditve = 1.38, 95% CI: 1.07 to 1.78) for individuals with cholesterol levels <200 mg/dL in the EPIC-Potsdam study. HRadditive was 1.06, 95% CI: 0.33 to 3.40 for individuals in the Heinz Nixdorf Recall study. A borderline significant decrease in CVD risk was observed in subjects with cholesterol levels ≥200 mg/dL (HRadditve = 0.77, 95% CI: 0.58 to 1.03) in the EPIC-Potsdam study. A similar trend was observed in the independent cohort (HRadditve = 0.60, 95% CI: 0.29 to 1.25). Conclusions Our study suggests an interaction between MTTP -164T > C functional polymorphism with total cholesterol levels. Thereby risk allele carriers with low cholesterol levels may be predisposed to an increased risk of developing CVD, which seems to be abolished among risk allele carriers with high cholesterol levels.